Rigorous LiDAR Strip Adjustment with Triangulated Aerial Imagery - Y. J. Zhang; X. D. Xiong; X. Y. Hu (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2013)
This paper proposes a POS aided LiDAR strip adjustment method. Firstly, aero-triangulation of the simultaneously obtained aerial images is conducted with a few photogrammetry-specific ground control points. Secondly, LiDAR intensity images are generated from the reflectance signals of laser foot points, and conjugate points are automatically matched between the LiDAR intensity image and the aero-triangulated aerial image. Control points used in LiDAR strip adjustment are derived from these conjugate points. Finally, LiDAR strip adjustment of real data is conducted with the POS aided LiDAR strip adjustment method proposed in this paper, and comparison experiment using three-dimensional similarity transformation method is also performed. The results indicate that the POS aided LiDAR strip adjustment method can significantly correct the planimetric and vertical errors of LiDAR strips. The planimetric correction accuracy is higher than average point distance while the vertical correction accuracy is comparable to that of the result of aero-triangulation. Moreover, the proposed method is obliviously superior to the traditional three-dimensional similarity transformation method.